1982
DOI: 10.3109/00016348209156568
|View full text |Cite
|
Sign up to set email alerts
|

Massive Hyperstimulation and Borderline Carcinoma of the Ovary

Abstract: A patient with persistent ovarian cysts subsequent to clomiphene-induced severe hyperstimulation was found to have borderline ovarian carcinoma. Since several endocrine and epidemiological studies implicate hormonal factors in the genesis of ovarian tumors, a possible association between ovarian hyperstimulation and neoplasia is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…Only one patient (case #4) had been treated with an unusual medication, clomiphene citrate. Although this drug has anecdotally been associated with testicular [20] and ovarian [21] neoplasms, we are unaware of any association between clomiphene citrate and Hodgkin's disease. Several authors have suggested that hematologic malignancies are rare in patients with sickle hemoglobinopathy [1,3,11].…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient (case #4) had been treated with an unusual medication, clomiphene citrate. Although this drug has anecdotally been associated with testicular [20] and ovarian [21] neoplasms, we are unaware of any association between clomiphene citrate and Hodgkin's disease. Several authors have suggested that hematologic malignancies are rare in patients with sickle hemoglobinopathy [1,3,11].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of malignancy appears to be low (Lais et al, 1988); a recent study using transvaginal ultrasonography to predict ovarian malignancy demonstrated a sensitivity of 100% and a negative predictive value of 100% (Sassone et al, 1991), and 60.6% of the cysticsepta tumours measuring 30-80 mm in diameter identified by echography resolve spontaneously within 3 months (Pinotti et al, 1988). However, it should be emphasized that persistent enlarged/ hyperstimulated ovaries in patients treated with follicular stimulants may mask ovarian neoplasm and result in a delay of the correct diagnosis (Atlas and Menczer, 1982;Bamford and Steele, 1982;Ben-Hur et al, 1986;Carter and Joyce, 1987). In the case presented here, the 'follicular structure' of the tumour which looked like a hyperstimulated ovary, could make ultrasonic diagnosis much more difficult.…”
Section: Discussionmentioning
confidence: 79%
“…Can ovarian stimulation or IVF be proposed to these patients when several studies incriminate hyperstimulation in the onset of ovarian cancer and borderline tumors? (3)(4)(5) This attitude is debated because the link between ovarian stimulation and the risk of ovarian cancer remains unclear.…”
Section: Discussionmentioning
confidence: 98%